Mask reuse during the COVID-19 pandemic: a national survey in Taiwan. (20th October 2021) - Hu, HY; Cheng, FS; Yen, YF; Lin, SY; Weng, SH; Chou, YC; Chu, DC; Chen, CC
Abstract: Background: The use of masks is an effective measure to prevent severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infection; however, mask reuse is not recommended. Studies examining the factors associated with mask reuse during the coronavirus disease (COVID-19) pandemic are limited. This nationwide survey aimed to determine the prevalence and factors associated with mask reuse among Taiwanese citizens during the pandemic. Methods: From May 18 through May 31, 2020, a computer-assisted telephone interview system was used to randomly select Taiwanese citizens who were interviewed for COVID-19 preventive behaviors and knowledge on the usage of masks. Multivariate logistic regression was used to identify factors associated with mask reuse during the COVID-19 pandemic. Moreover, generalized estimating equations (GEE) were used to analyze the rate of mask reuse among participants before and during the pandemic. Results: For a total of 1, 075 participants, the overall mean age was 57.4 years, and 82.2% of participants reported mask reuse during the COVID-19 pandemic. After controlling for other covariates, participants who had a greater knowledge on mask usage or had a high supply of masks were less likely to reuse masks during the pandemic. GEE analysis showed that compared with the participants' mask wearing behaviors before the COVID-19 pandemic, they were more likely to reuse masks during the pandemic. Conclusions: The rate of mask reuse among the general population during the pandemic was significantly higher than that before the pandemic. Individuals were less likely to reuse masks if they had adequate knowledge on mask usage or had a high supply of masks. Since mask reuse is associated with a higher risk of COVID-19 due to the possibility of wearing SAS-CoV-2-contaminated masks, it is imperative to educate people on the correct usage of masks. Further, the government should provide sufficient masks to the general population to decrease the reuse of masks. Key messages: Mask reuse increased during the COVID-19 pandemic due to the shortage in supply. It is imperative to educate people about the correct usage of masks.